2010
DOI: 10.1089/dia.2009.0104
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Exposure Improves Blood Glucose Level and Muscle Oxidative Capacity in Rats with Type 2 Diabetes

Abstract: Exposure to hyperbaric oxygen reduces high blood glucose levels and improves oxidative capacities in the skeletal muscles of rats with diabetes, and these effects are maintained under normobaric conditions even after exposure to hyperbaric oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Fiber type shifts occur under a variety of conditions, such as growth, aging, disease, and increased or decreased muscle activity [34]. To our knowledge, no previous studies have reported the shift of all fibers to a single type-with the exception of our finding that the soleus muscles in adult rats with type 2 diabetes contain only type I fibers that have lower oxidative enzyme activity than type IIA and IIC fibers [9][10][11][12]. However, the mechanism underlying the complete shift of fibers to a single type in the soleus muscles of CP-Ex rats remains unclear.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Fiber type shifts occur under a variety of conditions, such as growth, aging, disease, and increased or decreased muscle activity [34]. To our knowledge, no previous studies have reported the shift of all fibers to a single type-with the exception of our finding that the soleus muscles in adult rats with type 2 diabetes contain only type I fibers that have lower oxidative enzyme activity than type IIA and IIC fibers [9][10][11][12]. However, the mechanism underlying the complete shift of fibers to a single type in the soleus muscles of CP-Ex rats remains unclear.…”
Section: Discussionmentioning
confidence: 70%
“…The skeletal muscles in patients with type 2 diabetes contain a lower percentage of high-oxidative fibers than those in healthy individuals [5][6][7][8]. Furthermore, we observed that the soleus muscles in rats with type 2 diabetes contain a lower percentage of high-oxidative fibers than those in non-diabetic rats [9][10][11][12].…”
Section: Introductionmentioning
confidence: 88%
“…The proportion of low-oxidative type I fibers in the soleus muscle decreases and high-oxidative type IIA and IIC fibers, which are not detected in the soleus muscle of type 2 diabetic rats 37,38) , are observed after hyperbaric oxygen 40) . Hyperbaric oxygen reduces high glucose levels in GK rats during postnatal development and improves oxidative capacity in the soleus and plantaris muscles, and these effects are maintained under normobaric conditions after hyperbaric oxygen 42) (Fig. 10).…”
Section: Effect Of Mild Hyperbaric Oxygenmentioning
confidence: 92%
“…Muscle fiber specification appears to be associated with type 2 diabetes as well as metabolic syndrome and hypertension [37][38][39][40][41][42] (Table 3). Yasuda et al 37,38) found that both obese Otsuka Long-Evans Tokushima fatty (OLETF) and nonobese Goto-Kakizaki (GK) rats as animal models of type 2 diabetes exhibit a decreased proportion of high-oxidative type IIA and IIC fibers and an increased proportion of low-oxidative type I fibers in the soleus muscle during postnatal development.…”
Section: Skeletal Muscle Characteristics Of Animal Modelsmentioning
confidence: 99%
“…In this context, hyperbaric oxygen treatment was reported to reduce blood-glucose levels in diabetic mice and rats. [19][20][21] Therefore, this study examined whether chronic high glucose (CHG) causes cellular hypoxia in rat INS-1 β cells, and whether hyperoxia can reverse glucotoxicityinduced inhibition of insulin secretion.…”
mentioning
confidence: 99%